Hypochlorite accident during endodontic therapy with nerve damage – A case report - Perotti, Silvia; Bin, Paola; Cecchi, Rossana (Acta Biomedica Atenei Parmensis, 2018)
Endodontic therapy is a routinely practised clinical procedure with few reported complications but, as a bleaching agent, inadvertent spillage of sodium hypochlorite beyond the root canal system may result in extensive soft tissue or nerve damage, and even airway compromise. Although very rare, complications arising from hypochlorite extrusion beyond the root apex are described. NaOCl causes oxidation of protein and lipid membrane and causes necrosis, hemolysis and dermal ulcerations (2-4). Neurological complication are very rare. Paraesthesia and anaesthesia may affect the mental, inferior dental and infra-orbital branches of the trigeminal nerve and normal sensation may take many months to completely resolve (6, 7). Nerve damage (the buccal branch) was described in 2005 by Witton et al. (8) and patients exhibited a loss of the naso-labial groove and a down turning of the angle of the mouth and the motor function was regained after several months. We present a case in which the extrusion of NaOCl solution during endodontic therapy led to important destructive effects on soft tissues and nerves. The arisen medico legal issues are discussed.